Challenge of languages to speech therapists in India - Rathna N (Journal of All India Institute of Speech and Hearing, 1970)
This paper is nofiUtsearch report; it only intends to underline a problem faced by Speech and Hearing therapists in India, and to indicate some tentative solutions to this problem unique to us. The stimulus for this paper came from the enquiries received by us for Speech and Hearing therapists. Many of them insisted that the person should be a native speaker of the language spoken in the area. It seems to be a tacit assumption that it is essential for a Speech Pathologist and Audiologist to be a native speaker of the language his cases speak. Corder (1966) assumes that the therapist is himself 'of course normally a native speaker of the language of his patients'. Corder was writing in the British Journal of Disorders of Communication and his assumption might be very valid in the U.K. Can we automatically transport that assumption to India? No. This assumption is not valid in India, not at least at present and as I see it, it will not be in the foreseeable future. The reasons for this are many and we will look at them later. Can we at least assert that though the therapist is not a native speaker he should at least be well versed in the language? Should we insist on this at the time of employment as is being done in several places? The answer again is no, not reasonable. Am I saying that knowledge of the language of the cases is not useful to a therapist? No, not at all. It is extremely useful and hence desirable; but it is not alwayspossible to achieve and it is not essential